Inter-epitope spacer variation within polytopic L2-based human papillomavirus antigens affects immunogenicity - Zhang, Yueru; Mariz, Filipe Colaco; Sehr, Peter; Spagnoli, Gloria; Koenig, Karl Moritz; Çelikyürekli, Simay; Kreuziger, Tim; Zhao, Xueer; Bolchi, Angelo; Ottonello, Simone; Müller, Martin (npj vaccines, 2024)
The human papillomavirus minor capsid protein L2 is being extensively explored in pre-clinical studies as an attractive vaccine antigen capable of inducing broad-spectrum prophylactic antibody responses. Recently, we have developed two HPV vaccine antigens - PANHPVAX and CUT-PANHPVAX- both based on heptameric nanoparticle antigens displaying polytopes of the L2 major cross-neutralizing epitopes of eight mucosal and twelve cutaneous HPV types, respectively. Prompted by the variable neutralizing antibody responses against some of the HPV types targeted by the antigens observed in previous studies, here we investigated the influence on immunogenicity of six distinct glycine-proline spacers inserted upstream to a specific L2 epitope. We show that spacer variants differentially influence antigen immunogenicity in a mouse model, with the antigen constructs M8merV6 and C12merV6 displaying a superior ability in the induction of neutralizing antibodies as determined by pseudovirus-based neutralization assays (PBNAs). L2-peptide enzyme-linked immunosorbent assay (ELISA) assessments determined the total anti-L2 antibody level for each antigen variant, showing for the majority of sera a correlation with their repective neutralizing antibody level. Surface Plasmon Resonance revealed that L2 epitope-specific, neutralizing monoclonal antibodies (mAbs) display distinct avidities to different antigen spacer variants. Furthermore, mAb affinity toward individual spacer variants was well correlated with their neutralizing antibody induction capacity, indicating that the mAb affinity assay predicts L2-based antigen immunogenicity. These observations provide insights on the development and optimization of L2-based HPV vaccines.